Mahasantri's Interest in Investing Gold Tubes at Sharia Pawnshops - Winda Ainurrahmi; Anggun Citra Wardani; Arief Jaka Prima; Herlina Yustati (Sharia Economic and Management Business Journal (SEMBJ), 2024)
College students are a millennial generation with a high level of religiosity. As a millennial generation, they should have the intelligence to manage their finances and life management. One way that can be done is by investing. An investment that is easily made by Mahasantri is a gold tube investment. Where the price is affordable for student pockets and has less risk because the price of gold will continue to rise in the future. This research is field research with a qualitative approach. The type of this research is descriptive, with a population of Ma'had Al-Jami'ah UIN FAS Bengkulu students and a sample of 10 randomly selected students. The results of this study indicate that the mahasantri's interest in investing in gold tubes in Islamic pawnshops is influenced by several factors, namely knowledge, perceived convenience, and risk.